2018
DOI: 10.4103/aer.aer_76_18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combination of esmolol and diltiazem for attenuating hemodynamic response to laryngoscopy and intubation: A prospective randomized study

Abstract: Background:Laryngoscopy and tracheal intubation (LTI) are known to release catecholamines resulting in rise in heart rate (HR) and blood pressure. Various drugs have been studied till date to attenuate the sympathomimetic effects of laryngoscopy and intubation.Aims:The aim is to study the effect and safety of esmolol, diltiazem, and their combination on pressor response of laryngoscopy and intubation.Setting and Design:This prospective, randomized double-blind study was designed to assess the efficacy of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In another study, more bradycardia was observed with esmolol but without hemodynamic instability 19 . Other studies have demonstrated hemodynamic benefits for orotracheal intubation 20 and reduced myocardial oxygen consumption by preventing adverse events during surgery 21 .…”
Section: ■ Discussionmentioning
confidence: 98%
“…In another study, more bradycardia was observed with esmolol but without hemodynamic instability 19 . Other studies have demonstrated hemodynamic benefits for orotracheal intubation 20 and reduced myocardial oxygen consumption by preventing adverse events during surgery 21 .…”
Section: ■ Discussionmentioning
confidence: 98%
“…It can also lead to cerebrovascular accidents in hypertensive patients with cerebrovascular disease. 12 Various drug including β-blockers such as Labetalol, 13 and Esmolol, 14 Opioids, Lidocaine, 15,16 Nitroglycerine, alpha adrenergic agonists such as Clonidine, 17 and dexmedetomidine, 17 calcium channel blockers such as Diltiazem, 18 and have been used for obtunding the stress response. Lidocaine, whether given intravenously or through an endotracheal tube, successfully prevents the rise in blood pressure but fails to prevent the rise in heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] In addition, various drugs have been used to suppress the cardiovascular response of MLS, including intravenous infusion drugs (including propofol, dexmedetomidine, lidocaine, β-blockers or esketamine), inhalation sevoflurane, and oral drugs (such as clonidine and gabapentin). 17,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] However, propofol could delay anesthesia recovery, β-blockers could increase perioperative cardiac complications, and oral administration has a slow onset of action. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] Therefore, the efficacy of these techniques seems to be unreliable based on the variable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…17,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] However, propofol could delay anesthesia recovery, β-blockers could increase perioperative cardiac complications, and oral administration has a slow onset of action. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] Therefore, the efficacy of these techniques seems to be unreliable based on the variable outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation